DIMENSIONS AND INDICATORS OF RELIGIOSITY - JARMOCH, Edward (HUMANITARIAN STUDIES: HISTORY AND PEDAGOGY, 2022)
Religion in every culture and society is a significant social phenomenon. Sociology does not explain where religion came from and what its essence consists of, but it deepens the knowledge of religious phenomena as far as they depend on contact, activities, relations and social groups. Religion for her is a social fact. Faith, beliefs, values and religious activities are structural elements of religious systems. Internalized values, expressed in the attitudes and behaviors of religious communities, can be called religiosity, and religion itself can be treated as a cultural value and social reality. Faith has its visible manifestations in the socio-religious life of man, but it does not fully reflect the whole religiousness. Religiosity in the dimension of global attitudes towards faith in Poland was at a high level in the totalitarian system and at an even higher level in the system of nascent democracy in the first nineties of the last century. Currently, the indicators of believers are at a lower level. In turn, religious knowledge is related to the professed faith and may intensify its intensity. Although religious knowledge is the least likely to change in any environment, partly because it is of a low standard, a certain minimum of this knowledge is needed to accept and profess faith. In the intellectual dimension of religiosity, basic catechism knowledge as its integral element is insufficient in the present reality. Beliefs are closely related to the faith of members of a given religious community and are based on religious beliefs that reveal ideas about the nature of God's reality and its purpose. They are at a relatively high level and the selectivity of the dogmas of faith is more related to eschatological content. In their religious experience, almost half of Poles spoke positively about the possibility of feeling close to God in everyday life. Women are more likely to experience closeness to God than men. Young people experienced God the most in suffering, illness and loss of a loved one, as well as in prayer. Fulfillment of one-time religious practices is very high. For the Holy Mass more women than men attend once or several times a week. The vast majority of children grew up in a family home where there was a cross or an icon in the apartment. Identification with the parish church is greater in the rural environment than in the urban environment. The inhabitants of the city show far less interest in parish life. In turn, the portrait of the priest is drawn with his individual features: he is a confidant priest, with a good heart, oscillating between the sacred and the profane. Religious morality changes the most, in the direction of departing from the valid assessments and moral norms set by the Church, especially in the field of Catholic sexual ethics of marriage and family life. The young generation, when expressing opinions on various human behaviors, is slowly moving away from rigorism and towards understanding tolerance.